2013
DOI: 10.1136/bmjopen-2013-003036
|View full text |Cite
|
Sign up to set email alerts
|

Associations of metabolic factors and adipokines with pain in incipient upper extremity soft tissue disorders: a cross-sectional study

Abstract: ObjectivesEarlier studies have suggested associations between metabolic factors and musculoskeletal pain or disorders. We studied the associations of obesity, lipids, other features of the metabolic syndrome and adipokines (adiponectin, leptin, resistin, visfatin) with upper extremity pain in a clinical population with incipient upper extremity soft tissue disorders (UESTDs).DesignA cross-sectional study.SettingPrimary healthcare (occupational health service) with further examinations at a research institute.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…Fourteen studies examined biochemical mediators and markers related to inflammatory processes (33, 34, 40-42, 59, 61-63, 67, 69-72). Seven found significant associations between inflammatory markers and MSD (34,40,42,59,62,63,69), while seven did not (33,41,61,67,(70)(71)(72). Where associations were found, all had increased levels of inflammatory substances in MSD cases or with increased MSD severity, except for two studies in which reduced levels of IL-8 and IL-18 were observed in cases (41,59).…”
Section: Secondary Screen-quality Assessment Overviewmentioning
confidence: 88%
See 3 more Smart Citations
“…Fourteen studies examined biochemical mediators and markers related to inflammatory processes (33, 34, 40-42, 59, 61-63, 67, 69-72). Seven found significant associations between inflammatory markers and MSD (34,40,42,59,62,63,69), while seven did not (33,41,61,67,(70)(71)(72). Where associations were found, all had increased levels of inflammatory substances in MSD cases or with increased MSD severity, except for two studies in which reduced levels of IL-8 and IL-18 were observed in cases (41,59).…”
Section: Secondary Screen-quality Assessment Overviewmentioning
confidence: 88%
“…No association was observed between serum CRP and rotator cuff tendinitis, adhesive capsulitis, or a mix of MSD of <1 month duration (33,34,41). No association was found between serum TNF-α levels (an acute inflammatory cytokine) and chronic neck pain (69), between serum IL-1 and IL-6 levels (a pleiotropic cytokine and myokine) and late stage carpal tunnel syndrome (70), or between four acute phase cytokines (IL-1α, IL-1β, IL6, TNF-α) and a mix of MSD as each were below detectable levels (41). Results were less mixed when using local sampling methods, eg, assays of analytes from muscle extracellular fluid obtained using microdialysis.…”
Section: Secondary Screen-quality Assessment Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The association of obesity with painful, nonweightbearing joints, such as the hand (20), is not in keeping with the mechanical overload pathway and suggests that the metabolic effect of obesity may be an important consideration systemically. Despite investigations into the significance of adipokines in other regions of the body (21,22), their association with foot pain has not been formally investigated. The aim of this study was therefore to investigate the association of fat mass and adipokines with prevalent and future foot pain in a large communitydwelling cohort of adults.…”
Section: Introductionmentioning
confidence: 99%